Elucidating mechanisms of action of environmental contaminants from Doce River in Brazilian fish embryos using metabolomics and chemometric methods - Flávia Y. Yamamoto; Larissa A. Batista; Mayara P. Santos; Carmen Bedia; Silvia Lacorte; Rivelino M. Cavalcante; Marco T. Grassi; Denis M. de Souza Abessa; Romà Tauler (Science of The Total Environment, 2025)

Accessibility of polycyclic aromatic hydrocarbon content in fishes from the region of the 2019 oil spill on the northeast Brazil coast - Abinoan S. Rodrigues; Thayane Cristina da S. Moreira; Rafael Garrett Dolatto; Jandyson Machado Santos; Marco T. Grassi; Licarion Pinto; Ana Paula S. Paim (Marine Pollution Bulletin, 2025)

How natural and anthropogenic factors should drive microplastic behavior and fate: The scenario of Brazilian urban freshwater - Fernando F. Sodré; Imisi M. Arowojolu; Maria C. Canela; Rodrigo S. Ferreira; Andreia N. Fernandes; Cassiana C. Montagner; Cristiane Vidal; Mariana A. Dias; Gilberto Abate; Leticia C. da Silva; Marco T. Grassi; Crislaine Bertoldi; et al. (Chemosphere, 2023)

Extracting light rare earth elements by applying electric field assisted mining technique - Carolina M.G. Pires; Haroldo A. Ponte; Marco T. Grassi; Maria José J.S. Ponte; Alexandra B. Ribeiro (Minerals Engineering, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Large-scale spatial dynamics of Drosophila suzukii in Trentino, Italy - Gabriella Tait; Alberto Grassi; Ferdinand Pfab; Cristina M. Crava; Daniel T. Dalton; Roger Magarey; Lino Ometto; Silvia Vezzulli; M. Valerio Rossi-Stacconi; Angela Gottardello; Andrea Pugliese; Giuseppe Firrao; et al. (Journal of Pest Science, 2018)

Behavior of Atrazine and Its Degradation Products Deethylatrazine and Deisopropylatrazine in Oxisol Samples - Maristela F. Amadori; Marcio B. Rodrigues; Caio C. Rebouças; Patricio G. Peralta-Zamora; Marco T. Grassi; Gilberto Abate (Water, Air, & Soil Pollution, 2016)

Drosophila suzukii population response to environment and management strategies - Nik G. Wiman; Daniel T. Dalton; Gianfranco Anfora; Antonio Biondi; Joanna C. Chiu; Kent M. Daane; Beverly Gerdeman; Angela Gottardello; Kelly A. Hamby; Rufus Isaacs; Alberto Grassi; Claudio Ioriatti; et al. (Journal of Pest Science, 2016)

Gokyo Khumbu/Ama Dablam Trek 2012: effects of physical training and high-altitude exposure on oxidative metabolism, muscle composition, and metabolic cost of walking in women - E. Tam; P. Bruseghini; E. Calabria; L. Dal Sacco; C. Doria; B. Grassi; T. Pietrangelo; S. Pogliaghi; C. Reggiani; D. Salvadego; F. Schena; L. Toniolo; et al. (European Journal of Applied Physiology, 2016)

Fusarium spp. is able to grow and invade healthy human nails as a single source of nutrients - J. Galletti; M. Negri; F. L. Grassi; É. S. Kioshima-Cotica; T. I. E. Svidzinski (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Sequence analysis of human rotavirus strains: comparison of clinical isolates from Northern and Southern Italy - T. Grassi; F. Bagordo; A. Cavallaro; M. Guido; C. Malaventura; G. Gabutti; A. Donno (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Changes in Copper Speciation and Geochemical Fate in Freshwaters Following Sewage Discharges - Fernando F. Sodré; Marco T. Grassi (Water, Air, & Soil Pollution, 2007)

Ex-situ conservation of Black poplar in Europe: genetic diversity in nine gene bank collections and their value for nature development - V. Storme; A. Vanden Broeck; B. Ivens; D. Halfmaerten; J. Van Slycken; S. Castiglione; F. Grassi; T. Fossati; J. E. Cottrell; H. E. Tabbener; F. Lefèvre; C. Saintagne; et al. (Theoretical and Applied Genetics, 2004)

Molecular analysis of natural populations of Populus nigra L. intermingled with cultivated hybrids - T. Fossati; F. Grassi; F. Sala; S. Castiglione (Molecular Ecology, 2003)
In this study six simple sequence repeats (SSR or microsatellites) were selected for their ability to fingerprint a total of 60 commercial clones of Populus deltoides Marsh. and Populus × canadensis Moench (typically derived from crosses between Populus nigra L and P. deltoides ) and to characterize a natural population of P. nigra growing along the Ticino river in the North of Italy. Out of six SSRs used, four microsatellite loci were found to have alleles which were species‐specific to P. deltoides and could therefore be used as markers for introgression of P. deltoides into P. nigra . In the studied region hybrid poplars and P. deltoides commercial clones are cultivated as monoclonal stands close to the area where black poplar has its natural habitat. SSR analysis was performed to investigate whether there was evidence of introgression between the natural population and the monoclonal plantations of hybrids and P. deltoides clones cultivated in the surrounding area. Three stages of the natural population were analysed: a group of old trees about a hundred years old, a younger population (aged 2–30 years) and the seedlings of three females of this population. Alleles specific to P. deltoides were detected only in the old cohort of the natural population, while no introgression was observed in the younger individuals and their progenies. These results were also confirmed by isozyme analysis of loci PGI‐B, PGM and LAP‐A, which were previously identified as diagnostic for P. nigra , P. deltoides and P. × canadensis .

Special Contribution: An Overview of Recent Seismic Refraction Experiments in Central Europe - A. Guterch; M. Grad; A. Špičák; E. Brückl; E. Hegedüs; G.R. Keller; H. Thybo; K. Aric; S. Acevedo; I. Asudeh; M. Behm; A. A. Belinsky; et al. (Studia Geophysica et Geodaetica, 2003)

Isolation of Cytotoxic Aeromonas spp. from Food - M.A. Grassi; T. Civera; R.M. Turi (Veterinary Research Communications, 2003)